Environmental microplastics disrupt swimming activity in acute exposure in Danio rerio larvae and reduce growth and reproduction success in chronic exposure in D. rerio and Oryzias melastigma. (1st September 2022) - Cormier, Bettie; Cachot, Jérôme; Blanc, Mélanie; Cabar, Mathieu; Clérandeau, Christelle; Dubocq, Florian; Le Bihanic, Florane; Morin, Bénédicte; Zapata, Sarah; Bégout, Marie-Laure; Cousin, Xavier
Abstract: Microplastics (MPs), widely present in aquatic ecosystems, can be ingested by numerous organisms, but their toxicity remains poorly understood. Toxicity of environmental MPs from 2 beaches located on the Guadeloupe archipelago, Marie Galante (MG) and Petit-Bourg (PB) located near the North Atlantic gyre, was evaluated. A first experiment consisted in exposing early life stages of zebrafish ( Danio rerio ) to MPs at 1 or 10 mg/L. The exposure of early life stages to particles in water induced no toxic effects except a decrease in larval swimming activity for both MPs exposures (MG or PB). Then, a second experiment was performed as a chronic feeding exposure over 4 months, using a freshwater fish species, zebrafish, and a marine fish species, marine medaka ( Oryzias melastigma ). Fish were fed with food supplemented with environmentally relevant concentrations (1% wet weight of MPs in food) of environmental MPs from both sites. Chronic feeding exposure led to growth alterations in both species exposed to either MG or PB MPs but were more pronounced in marine medaka. Ethoxyresorufin-O-deethylase (EROD) and acetylcholinesterase (AChE) activities were only altered for marine medaka. Reproductive outputs were modified following PB exposure with a 70 and 42% decrease for zebrafish and marine medaka, respectively. Offspring of both species (F1 generation) were reared to evaluate toxicity following parental exposure on unexposed larvae. For zebrafish offspring, it revealed premature mortality after parental MG exposure and parental PB exposure produced behavioural disruptions with hyperactivity of F1 unexposed larvae. This was not observed in marine medaka offspring. This study highlights the ecotoxicological consequences of short and long-term exposures to environmental microplastics relevant to coastal marine areas, which represent essential habitats for a wide range of aquatic organisms. Graphical abstract: Image 1 Highlights: Environmental MPs led to weak toxic effects on zebrafish embryos and larvae. Chronic trophic exposure to MPs reduced growth and reproduction for both fish F0. Survival, growth, and behaviour of F1 larval offspring were affected by MPs. Different effects were observed depending on fish species and/or MPs origin. Chemical composition and not polymer type explained toxicity of environmental MPs.